RETRACTED: Analysis of the Legal Framework Governing Gas Flaring in Nigeria’s Upstream Petroleum Sector and the Need for Overhauling - Olusola Joshua Olujobi (Social Sciences)
Nigeria is rated the number one producer of crude oil in Africa. Still, oil exploration activities have resulted in a high rate of gas flaring due to weak enforcement of the anti-gas flaring laws by the regulatory authorities. Associated natural gas is generated from oil production, and it is burnt in large volumes, thereby leading to the emission of greenhouse gases and waste of natural resources which could have generated billions of dollars for the Federal Government of Nigeria. There are concerns that if nothing is done to curtail this menace, humans and the environment will be imperiled due to its negative consequences. There is therefore a need to decrease gas flaring by replicating the strategies applied in the selected case study countries to combat the menace. It is relevant to carry out this analysis to reduce greenhouse gas emissions in the oil industry for the sustainability of the energy sector and to generate more revenues for the government. This study provides guidelines for legislatures on suitable approaches to adopt for formulating an anti-flaring legal framework. The study is a comparative analysis of national legal regimes on gas flaring in Nigeria, Canada, the United Kingdom, Saudi Arabia, and Norway. The study adopts a doctrinal legal research method, a point-by-point comparative approach with a library-based legal research method. The study finds that weak enforcement of laws is a critical factor responsible for the menace. It recommends the use of more advanced technologies, a sophisticated mixture of regulations and non-regulatory incentives such as fiscal policies and gas market restructuring, and proffers further suggestions based on the lessons learnt from the selected case study countries.